The Emerging Role of Mesenchymal Stem Cells in Vascular Calcification - Changming Xie; Liu Ouyang; Jie Chen; Huanji Zhang; Pei Luo; Jingfeng Wang; Hui Huang (Stem Cells International)
Vascular calcification (VC), characterized by hydroxyapatite crystal depositing in the vessel wall, is a common pathological condition shared by many chronic diseases and an independent risk factor for cardiovascular events. Recently, VC is regarded as an active, dynamic cell-mediated process, during which calcifying cell transition is critical. Mesenchymal stem cells (MSCs), with a multidirectional differentiation ability and great potential for clinical application, play a duplex role in the VC process. MSCs facilitate VC mainly through osteogenic transformation and apoptosis. Meanwhile, several studies have reported the protective role of MSCs. Anti-inflammation, blockade of the BMP2 signal, downregulation of the Wnt signal, and antiapoptosis through paracrine signaling are possible mechanisms. This review displays the evidence both on the facilitating role and on the protective role of MSCs, then discusses the key factors determining this divergence.